Reinfection by hepatitis C virus following effective all-oral direct-acting antiviral drug therapy in HIV/hepatitis C virus coinfected individuals. (15th March 2019) - Berenguer, Juan; Gil-Martin, Ángela; Jarrin, Inmaculada; Montes, María L.; Domínguez, Lourdes; Aldámiz-Echevarría, Teresa; Téllez, María J.; Santos, Ignacio; Troya, Jesús; Losa, Juan E.; Serrano, Regino; De Guzmán, María T.; et al.
Abstract : Objectives: We analysed hepatitis C virus (HCV) reinfection among participants in a prospective registry of HIV/HCV-coinfected patients treated with all-oral direct-acting antiretroviral (DAA)-based therapy in the region of Madrid. Design: An observational cohort study. Methods: The study period started on the date sustained viral response (SVR) was confirmed. The censoring date was 31 December 2017. SVR was defined as negative HCV-RNA 12 weeks after completion of treatment. Reinfection was defined as a positive HCV-RNA test result after achievement of SVR. Results: Reinfections were detected in 17 of 2359 HIV/HCV-coinfected patients (0.72%) overall, in 12 out of 177 (6.78%) MSM and in five out of 1459 (0.34%) people who inject drugs (PWID). The incidence of reinfection [95% confidence interval (95% CI)] per 100 person-years was 0.48 (0.30–0.77) overall, 5.93 (3.37–10.44) for MSM and 0.21 (0.09–0.52) for PWID. Reinfections were detected a median of 15 weeks (interquartile range 13–26) after SVR. In 10 (58.82%) patients, the reinfection was caused by a different HCV genotype. All 12 MSM with reinfection acknowledged unprotected anal intercourse with several partners, seven used chemsex, six reported fisting and four practiced slamming. A concomitant STI was detected in five patients. Four IDU with reinfection reported injecting drugs following SVR. Conclusion: HCV reinfection is a matter of concern in HIV-positive MSM treated with all-oral DAA therapy in the region of Madrid. Our data suggest that prevention strategies and frequent testing with HCV-RNA should be applied following SVR in MSM who engage in high-risk practices.